Adsorption of endocrine disrupting compounds and other emerging contaminants using lignocellulosic biomass-derived porous carbons: A review - U.A. Qureshi (17100274) (2020)
Hydrochars from lignocellulose biomass have received an upsurge of interest in different fields, especially in the area of adsorption. Hydrothermally produced hydrochars are effective adsorbents for removing different pollutants, and they serve as a cheap and sustainable raw material for subsequent activation to achieve porous activated carbons (ACs) with large surface areas. In this review, recent studies on preparation and characteristics of adsorbents in terms of hydrochars from lignocellulose biomass and their derived ACs are presented and discussed. The application of these adsorbents for the removal of endocrine disrupting chemicals and other emerging pollutants is included. The sources and classification, adsorption isotherm, kinetics, and mechanism of these pollutants and the capability of regenerating and reusing cheap and efficient adsorbents such as hydrochar and ACs are also discussed. This review identifies knowledge gaps and proposes insights into new directions for improving the applications of hydrochar and ACs as adsorbents. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2020.101380